A 9-Channel Phase Coherent Receive System for Direction of Arrival Estimation - Depold, Andreas; Dorn, Christian; Erhardt, Stefan; Weigel, Robert; Lurz, Fabian (European Microwave Week 2021, 2022)
Collapsed buildings are a common occurrence after earthquakes, but are also commonly caused by gas explosions. The survival chance of buried victims is heavily dependent on the time it takes to locate and rescue them. This paper introduces a 9-channel phase coherent receive system intended for direction finding in search and rescue applications. The motivation for this system is to minimize the time necessary to locate the buried phones of victims. The design consists of an FPGA based digital system with high speed I/O for data acquisition and signal processing, as well as nine synchronized receivers each covering the entire target bandwidth. A high phase resolution is achieved down to very low input level

A Light Weight 3x3 Switched Polarity URA Antenna and Receive System for Direction Finding - Depold, Andreas; Dorn, Christian; Erhardt, Stefan; Weigel, Robert; Lurz, Fabian (2022 IEEE Topical Conference on Wireless Sensors and Sensor Networks, WiSNeT 2022, 2022)
Minimizing the time it takes to locate and rescue victims from building collapses is critical for their survival chance. This scenario causes a challenging environment for radio frequency based localization. This paper introduces a direction finding system based on a 3x3 uniform rectangular array with integrated polarization switching for multipath mitigation intended for search and rescue applications. It is shown that utilizing two polarizations can be used to reduce or eliminate ambiguities caused by multipath propagation. Further approaches to optimize localization ability are discusse
CRIS-Team Scopus Importer:2022-04-15
Keywords: Antenna arrays; Direction-of-arrival estimation; phase detection; receivers

A multi-PMT optical module for the IceCube upgrade - Dorn, Christian; Kossatz, M.; Kretzschmann, A.; Ortjohann, H. W.; Reubelt, Jonas; Sulanke, K. H.; Weigel, Robert; Classen, Lew; Kappes, Alexander; Karg, Timo (Proceedings of Science, 2019)
Following the first observation of an astrophysical high-energy neutrino flux with the IceCube Neutrino Observatory in 2013 and the identification of a first cosmic high-energy neutrino source in 2017, the detector will be upgraded with about 700 new advanced optical sensors. This will expand IceCube's capabilities both at low and high neutrino energies. A large fraction of the upgrade modules will be multi-PMT Digital Optical Modules, mDOMs, each featuring 24 three-inch class photomultiplier tubes (PMTs) pointing uniformly in all directions, thereby providing an almost homogeneous angular coverage. The signal from each PMT is digitized individually, providing directional information for the incident photons. Together, the 24 PMTs provide an effective photosensitive area more than twice than that of the current IceCube optical module. The main mDOM design challenges arise from the constraints on the module size and power needed for the 24-channel high-voltage and readout systems. This contribution presents an mDOM design that meets these challenges and discusses the sensitivities expected from these modules.
CRIS-Team Scopus Importer:2021-04-20

Digital Phase Correction for Multiplexed ADCs in Low-Cost Six-Port Interferometers - Lurz, Fabian; Dorn, Christian; Lindner, Stefan; Linz, Sarah; Mann, Sebastian; Weigel, Robert; Kölpin, Alexander (IEEE Topical Conference on Wireless Sensors and Sensor Networks (WiSNet), 2016)
elib2cris::1512001600,lurz2016

Low-Cost Direction-of-Arrival Measurements using Multiplexed Antenna Switching - Dorn, Christian; Erhardt, Stefan; Weigel, Robert; Kölpin, Alexander; Lurz, Fabian (Wireless Sensors and Sensor Networks, 2020)